The influence of taqwa in sustainable capacity building - Mhd. Sarif, Suhaimi (Zes Rokman Resources, 2016)
Sustainable capacity building in the dynamic and competitive business markets enables firms to be ready to face the challenges and uncertainty. There are many factors contribute to the sustainable capacity building for dynamism and competitiveness. Taqwa provides internal defense for firms in terms of readiness and willingness and external dynamism in terms of proactive actions and strategies. The purpose of this paper is to explore the influence of taqwa in providing sustainability in the capacity building in achieving competitive advantage and outstanding performance against the competitors. The study interviewed top management of selected large corporations. The results of the study showed three areas of influence of taqwa in providing sustainable capacity building for firms. Firstly, taqwa provides the firms the ability to keep the momentum to be consistent (istiqamah) in the efforts to gain competitiveness. Secondly, taqwa influences the conviction of the firms to be firm and steadfast (qawiy). Finally, taqwa enables them to be great. Future research should extend the respondents among top management from different companies. The use of case study method should be considered for in-depth analysis on the participating companies.